Implementation of Grounded Theory to Analyze the Effect of Social Media Functionality on MSME Market Segmentation in Indonesia - Annisa, Lolanda Hamim; Saridewi, Larasati Puspita (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
Empowering SMEs in the midst of globalization and high competition has forced MSMEs to face global challenges, such as increasing innovation, developing human resources and technology, and expanding the marketing area. Social networks provide a medium for processing new innovations for SMEs such as relationships with customers, work partners and also suppliers. Business process management can assist business actors in carrying out their business activities in the face of today's challenges and global competition. This study reveals that every business process can be supported by the implementation of IT by a company. This study uses a grounded theory approach. Grounded theory studies tend to follow a structured approach. This research uses case studies of hydroponic SMEs in Indonesia, which produce the types of social media & social media functions that are often used by Indonesians. The main strength of this research is the functions of social media needed by SME actors. From the results of the study it was found that SMEs need social media functionality in 4 functions, namely: the interaction function, the marketing function, the reputation function, and the information function. SMEs in Indonesia need applications that contain these 4 functions to be able to market, sell, and interact with other people.